Prevalence of Anxiety, Depression and Stress Symptoms and its Association with Neck/Shoulder Pain in Adolescents Athletes - Hítalo Andrade Silva; Muana Pereira Passos; Valéria Alves Oliveira; Yslainy Araújo Silva; Ana Carolina Rodarti Pitangui; Rodrigo Cappato Araújo (Desafio Singular, 2018)
Psychological distress is among the main causes of the onset or worsening of pain symptoms in young sports people. The increasing participation of adolescents in various sports increases the need to verify the prevalence and association of these affective disorders such as anxiety, stress and depression with pain in the shoulder girdle and in the cervical region that are typical in sportspeople who use more frequently the upper limbs. The sample (n = 310; 14.16±2.12 years). Corlett's body diagram and the Brazilian short version of the anxiety, depression and stress scale (DASS-21) were used. Independent t-tests, chi-square and multiple logistic regression were used. The girls had a higher prevalence of anxiety/stress (62%, p = 0.02). The variables associated with anxiety/stress were female (OR = 2.16), aged 15 to 19 years (OR = 2.39) and individual modality (OR = 1.88). The variables associated with depression were age 15 to 19 years (OR = 1.74), individual modality (OR = 1.84) and pain in the shoulder girdle and cervical region (OR = 2.33).